2009
DOI: 10.3917/cdge.046.0017
|View full text |Cite
|
Sign up to set email alerts
|

Le renouveau des régimes de genre en Allemagne et en Suisse : bonjour ‘néo maternalisme’ ?

Abstract: Résumé Cet article s’interroge sur la dynamique des régimes de genre en Allemagne et en Suisse de manière comparée et diachronique. Il propose pour commencer une grille analytique des régimes de genre. Il retrace ensuite les contours du modèle traditionnel du régime de genre en Allemagne et en Suisse, avant de comparer les dynamiques discursives observées récemment dans ces deux pays puis d’explorer leur implication. En conclusion, les arrangements sociaux et politiques expliquant les dynamiques observées sont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 13 publications
0
15
0
6
Order By: Relevance
“…On the other hand, the care system is mostly relegated to private institutions, and the public policies targeting work-family reconciliation are less robust than those of other western welfare states (Monnier 2006): school schedules are hardly compatible with those of parents who work, and expensive public child care and marriage-based taxation discourage women's labour force participation (Bütler and Ruesch 2007). These welfare arrangements are based on the one-and-a-half-earner model, in which men work full time while women who become mothers adjust their working hours to accommodate their care obligations (Giraud and Lucas 2009). As a consequence, while Switzerland has a higher female labour market participation rate than many other European countries, most Swiss women are employed part time (Bühlmann et al 2012).…”
Section: The Swiss Context and Lone Mothers' Employmentmentioning
confidence: 99%
“…On the other hand, the care system is mostly relegated to private institutions, and the public policies targeting work-family reconciliation are less robust than those of other western welfare states (Monnier 2006): school schedules are hardly compatible with those of parents who work, and expensive public child care and marriage-based taxation discourage women's labour force participation (Bütler and Ruesch 2007). These welfare arrangements are based on the one-and-a-half-earner model, in which men work full time while women who become mothers adjust their working hours to accommodate their care obligations (Giraud and Lucas 2009). As a consequence, while Switzerland has a higher female labour market participation rate than many other European countries, most Swiss women are employed part time (Bühlmann et al 2012).…”
Section: The Swiss Context and Lone Mothers' Employmentmentioning
confidence: 99%
“…Peruvian women's access to university education and the labour market in Peruvian urban middle class have an impact on the dissociation between femininity and maternity, on the growing importance given to professional projects (Fuller, 2001), as well as on the practice of delaying family formation (Cieza, 2016). When abroad, these women's career aspirations might clash with Swiss restrictive migration (Riaño, 2011) and neo-maternalistic care regimes (Giraud & Lucas, 2009). In contrast with a binary vision that views home countries as sites of women's oppression and host countries as sites of women's emancipation, I found that the male breadwinner/female caregiver model persists in these highly skilled women's and men's transnational experiences between Peru and Switzerland.…”
Section: Introductionmentioning
confidence: 76%
“…The Swiss care and migration regimes particularly influence the feminization of highly skilled migration from Peru. 3 Firstly, the Swiss care regime has been labeled as neo-maternalist, based on a male breadwinner/female caregiver family model (Baghdadi, 2010;Giraud & Lucas, 2009;Giudici & Gauthier, 2009). When considering the presence of small children, it is possible to observe the increase of gender differences: only 9.6% of couples had two spouses working full time in 2015 (FSO, 2016b).…”
Section: Peruvian Women's and Men's Access To Education Employment mentioning
confidence: 99%
“…Ce rapport peut être plus où moins participatif et négocié, notamment quant à la définition des besoins des personnes dépendantes et de leurs proches ou aux savoir-faire mobilisés dans la relation de soin. Ainsi, le mode assistanciel et paternaliste sur lequel s'est développée l'offre de assistanciel et paternaliste sur lequel s'est développée l'offre de et paternaliste sur lequel s'est développée l'offre de care est aujourd'hui contesté pour son caractère infantilisant (Giraud et Lucas 2007). A travers l'usage qui en est fait, les instruments peuvent ici contribuer localement à reproduire une logique paternaliste dans le champ du care ou au contraire, à favoriser une forme d'« empowerment ».…”
Section: Politique Du Care Et Gouvernement De La Vieunclassified
“…Le second débat porte sur la conciliation entre famille et travail (Nicole-Drancourt 2009 ;Lebihan et Martin 2008) et la division sexuée des rôles sociaux. De ce point de vue et malgré de récentes percées en matière d'égalité, l'évolution des politiques du care en Suisse se heurte à un régime de genre encore marqué par une image traditionnelle de la femme comme principale pourvoyeuse de soin (Giraud et Lucas 2009).…”
Section: Introductionunclassified